Praktikalitas Media Pembelajaran Interaktif dalam Pembelajaran Mengevaluasi Informasi dalam Teks Negosiasi untuk Siswa SMA - Al Abil Hidayatullah; Dina Ramadhanti (Universitas Muhammadiyah Jember, 2026)
Learning media is used as a tool that helps teachers to teach and helps students to learn. Students need interactive learning media that is contextual, participatory, adaptive, and provides feedback to measure the achievement of learning objectives. This study aims to evaluate the practicality of interactive learning media in learning to evaluate information in negotiation texts. Using descriptive quantitative approach, this study involved 30 students and 3 subject teachers to give their responses to interactive learning media in learning to evaluate information in negotiation texts that have been designed and validated by experts. The research data was collected using a practicality questionnaire for teachers and students. The results showed that teachers and students stated that the interactive learning media on the material of evaluating information in negotiation texts were declared very practical. Teachers stated that the learning media was very practical with a percentage of 93.33% in the aspects of ease of use, time efficiency, usefulness, students' interest, and suitability for learning materials. Students also stated that the learning media was very practical with a percentage of 82.46% in the aspects of ease of use, involvement and interest, ease of understanding, support for learning, and suitability with learning materials. Thus, this interactive learning media can be used as a reference and tool for teachers and students to learn to evaluate information in negotiation texts.